Improving construction project performance through the project manager: an Indonesian experience - Yusof, Mohamad Nizam; Modifa, Ira; Bakar, Abu Hassan Abu; Razak, Arman Abdul (2008)

(untitled)
The project manager’s responsibilities are to plan and control company resources efficiently and to complete the project on schedule, within the budgeted costs and specified quality towards making the project a success. However, many reports show the opposite. Studies on this issue are pointing toward the poor understanding of good practice as a basic problem for the failures in project management. The objective of this paper is to study good practice of project management tools and techniques that can be applied by project managers in construction projects. This paper also measures how these tools and techniques were applied in construction projects. Using the case study approach which was carried out in Medan, Indonesia, three large projects were chosen, namely RSU Pirngadi, Plaza Medan Fair and the Redevelopment of Pasar Petisah. The data was collected as well as obtained from and through project reports, questionnaires and interviews with the project managers of the relevant projects. The variables were then separated into two classifications that could be defined as either success or failure. The findings of the research found that good project management practices result in a higher project performance.